Novel Oral Anti Coagulants (NOACs) as Anti Thrombotic on Atrial Fibrillation Patients - Sebayang, Abed Nego Okthara (Talenta Publisher, 2020)
ABSTRACT Atrial Fibrillation (AF) is an arrhythmia characterized by disorganization of atrial depolarization resulting in the impaired mechanical function of the atrium. Management of AF aims to prevent complications of ischemic stroke and systemic embolism, carried out by the administration of anticoagulant, warfarin, but warfarin has many side effects. New Oral Anticoagulants (NOAC) can be used as alternatives in preventing complications of AF.New anticoagulants such as dabigatran, rivaroxaban, and apixaban have better effects than other anticoagulants such as warfarin and have major side effects of bleeding and minimal relevant bleeding. Based on a national survey in Denmark to see a balance between stroke and intracranial bleeding, CHA2DS2-VASc 1 scores were only apixaban and both dabigatran doses (110 mg bid and 150 mg bid) which provided better clinical benefits than warfarin, but if the CHA2DS2- score VASc â‰¥2 of all NOACs is superior to warfarin. Atrial fibrillation can cause ischemic stroke and systemic embolism. New Oral Anticoagulant (NOACs) can be used as a solution to prevent complications from AF with minimal side effects. It is expected that the presence of new anticoagulants can reduce the rate of ischemic stroke and ischemic embolism due to AF with minimal side effects of bleeding and other side effects. Keywords: Anticoagulant, Atrial Fibrillation, NOAC, Warfarin ABSTRAK Atrial Fibrilasi (AF) adalah suatu aritmia yang ditandai dengan disorganisasi dari depolarisasi atrium sehingga berakibat pada gangguan fungsi mekanik atrium. Penatalaksanaan AF bertujuan mencegah komplikasiyakni stroke iskemik dan emboli sistemik, dilakukan dengan cara pemberian anti-koagulan yakni warfarin. Pemberian warfarin memiliki banyak efek samping. Novel Oral Anti Coagulants (NOAC) dapat dijadikan alternatif dalam mencegah komplikasi AF. Anti-koagulan baru seperti dabigatran, rivaroxaban dan apixaban memiliki efektifitas yang lebih baik daripada anti-koagulan lainnya seperti warfarin dan memiliki efek samping perdarahan mayor dan perdarahan relevan yang minimal. Berdasarkan survei nasional di Denmark untuk melihat keseimbangan antara stroke dan perdarahan intra-kranial didapatkan bila skor Congestive heart failure, Hypertension, Age â‰¥75 years (skor 2), Diabetes mellitus, Stroke history (skor 2), peripheral Vascular disease, Age between 65 to 74 years, Sex Category (female) dan â€œCâ€ adalah adanya disfungsi ventrikel kiri sedang hingga berat (Left Ventricular Ejection Fraction/LVEF â‰¤ 40%) CHA2DS2-VASc 1 hanya apixaban dan kedua dosis dabigatran (110 mg b.i.ddan 150 mg b.i.d) yang memberikan manfaat klinis yang lebih baik daripada warfarin, tetapi apabila skor CHA2DS2-VASc â‰¥2 seluruh NOAC lebih superior dibanding warfarin.AF dapat menyebabkan stroke iskemik dan emboli sistemik.NOAC dapat dijadikan solusi untuk mencegah komplikasi dari AF dengan efek samping yang minimal. Diharapkan dengan hadirnya anti-koagulan baru dapat menurunkan angka stroke iskemik dan emboli iskemik akibat AF dengan efek samping perdarahan dan efek samping lainnya yang minimal. Kata Kunci: Antikoagulan, Atrial Fibrilasi, NOAC, Warfarin